Pengaruh Kesadaran Masyarakat Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor: Studi Empiris Di Kabupaten Nagan Raya - Ningsih, Niken Rahayu; Marlina, Lilis; Fatmayanti, Fatmayanti (-, 2025)
This study aims to analyze the influence of public awareness on motor vehicle taxpayer compliance in Nagan Raya Regency. Public awareness is considered an internal factor that reflects individuals’ understanding, trust, and sense of responsibility in voluntarily fulfilling fiscal obligations. A quantitative approach was employed using a survey method involving 100 respondents who are active taxpayers. The data were analyzed using simple linear regression to examine the relationship between variables. The results indicate that public awareness has a positive and significant effect on taxpayer compliance. Individuals who understand their rights and obligations, trust in tax management, and possess a moral drive to pay taxes on time are more likely to comply with tax regulations. These findings highlight the importance of strengthening fiscal awareness as a strategic effort to improve regional tax compliance, particularly in the motor vehicle tax sector, which plays a vital role in contributing to Regional Original Revenue (PAD).